IMPLEMENTASI PENDIDIKAN CHARACTER BUILDING MELALUI PEMBELAJARAN TAHFIZH AL-QUR’AN DI SD IT BUNAYYA PADANGSIDIMPUAN - Rini Juliana; Rini Agustini; Hilmi Hilmi (Universitas Muhammadiyah Tapanuli Selatan, 2019)
Many factors can turn a child into a good character. One of the factors is through education of religious value, such as the Tahfidzul Qur'an, which can be a supporting factor for the formation of religious character. To pay attention to children's attention in rote learning must be taught with fun the teacher must understand the child's condition. Usually children get bored quickly to avoid this so we must know the child's character by diagnosing to form good character through learning Tahfidzul Qur’an.The problem that will be discussed in this research is: How is the implementation of character building education through tahfiz learning in Padangsidimpuan Elementary School? What are the roles of teachers and parents in implementing character building education through tahfiz learning at SD IT Padangsidimpuan? What are the supporting and inhibiting factors in implementing character building education through tahfiz learning at SD IT Padangsidimpuan?This research was conducted at Bunayya Padangsidimpuan Elementary School. Data analysis techniques in this study were qualitative data analysis, where data analysis was carried out interactively and took place continuously at each stage of the research so that the data was completely finished and saturated. Data collection was carried out through observation, interviews and documentation.Keywords: Implementation, Character Building, Learning, Tahfizh al-Qur'an